Intussusception in the first year of life: a UK national surveillance study. (29th September 2015) - Samad, L; Bashir, HE; Marven, S; Cameron, JC; Lynn, R; Sutcliffe, A; Taylor, B
Abstract : Background: Rotavirus infection is the commonest cause of severe childhood diarrhoea. This remains a major cause of death and illness but can be substantially reduced by vaccination. Initial attempts at rotavirus vaccination seemed to increase the risk of intussusception. Although trials with newer vaccines suggest no increased risk, the earlier finding may have adverse effects on vaccine acceptability. The only similar incidence study was carried out over a decade ago and found an annual incidence of 66 per 100 000 infants, using routinely collected Hospital Episode Statistics data for England. Aim: To estimate the current, national incidence of intussusception in infants in the UK and Ireland—prior to vaccine introduction. Methods: The authors carried out prospective active surveillance of intussusception from 1 March 2008 to 31 March 2009—the first joint collaboration between the British Paediatric Surveillance Unit (BPSU) and the British Association of Paediatric Surgeons. Clinicians were requested to notify cases of intussusception less than a year of age, using the established BPSU system supplemented by a special card to surgeons. Results: Overall, the completion rate after notification was 96.1% (367 study questionnaires received/382 cases notified). 254 cases were confirmed, 105 were reported more than once (the remaining eight were "probable/possible" cases). Two-thirds of confirmed cases were boys (64.6%) and the median age was 5.9 months (IQR=4.2–8.4 months). The authors found an annual incidence of intussusception among UK and Irish infants of 28 cases per 100 000 live births. The highest country incidence was observed in Northern Ireland (45) followed by Scotland (29), England (28) and Wales (18). In England, London showed the highest incidence (48) followed by North West (35), East Midlands (29), Yorkshire and the Humber (25), South West (24), East of England (21), South East (20), West Midlands (10) and North East (9). Conclusion: The incidence of intussusception appears to have declined over the last 20 years. Our study provides current national incidence, which is important to monitor changes in incidence following rotavirus vaccine exposure, and inform vaccine policy.